Noise-robust detection of peak-clipping in decoded speech - Eaton,J; Naylor,PA (2014)
Clipping is a commonplace problem in voice telecommunications and detection of clipping is useful in a range of speech processing applications. We analyse and evaluate the performance of three previously presented algorithms for clipping detection in decoded speech in high levels of ambient noise. We identify a baseline method which is well known for clipping detection, determine experimentally the optimized operation parameter for the baseline approach, and use this in our experiments. Our results indicate that the new algorithms outperform the baseline except at extreme levels of clipping and negative signal-to-noise ratios.